2017
DOI: 10.1002/anie.201702288
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)‐Catalyzed Bridged [5+2] Cycloaddition of cis‐Allene‐vinylcyclopropanes to Synthesize the Bicyclo[4.3.1]decane Skeleton

Abstract: Previously reported was that cis-ene-vinylcyclopropanes (cis-ene-VCPs) underwent Rh-catalyzed [5+2] reaction to give 5,7-fused bicyclic products, where vinylcyclopropane (VCP) acts as five-carbon synthon. Unfortunately, this reaction had very limited scope. Replacing the 2π component of cis-ene-VCPs to allene moiety, the corresponding cis-allene-VCPs did not undergo the expected normal [5+2] cycloaddition to give 5,7-fused bicyclic products. Instead, the challenging bicyclo[4.3.1]decane skeleton was obtained v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 77 publications
0
17
1
Order By: Relevance
“…Am ixture of the bicyclo-[4.3.1]decane products 2p-q and bicyclo[5.3.0]decane products 3p-q,the originally expected normal [5+ +2] cycloadducts, can be isolated for substrates 1p-q.F or 1p,w ith bulkier phenyl group,the product 3p was the major product and the structure was confirmed by X-ray crystallography. [26] In stark contrast to previous work (Scheme 1), the trans bicyclo-[5.3.0]decane product was achieved here.F inally,w et ested alonger tether, hoping to achieve the bicyclo[4.4.1]undecane product (Scheme 2). However no product could be observed and the starting material was recovered.…”
contrasting
confidence: 92%
See 1 more Smart Citation
“…Am ixture of the bicyclo-[4.3.1]decane products 2p-q and bicyclo[5.3.0]decane products 3p-q,the originally expected normal [5+ +2] cycloadducts, can be isolated for substrates 1p-q.F or 1p,w ith bulkier phenyl group,the product 3p was the major product and the structure was confirmed by X-ray crystallography. [26] In stark contrast to previous work (Scheme 1), the trans bicyclo-[5.3.0]decane product was achieved here.F inally,w et ested alonger tether, hoping to achieve the bicyclo[4.4.1]undecane product (Scheme 2). However no product could be observed and the starting material was recovered.…”
contrasting
confidence: 92%
“…Theb icyclo[4.3.1]decane skeleton of the product was further confirmed by singlecrystal X-ray crystallography analysis of 2k. [26] Unfortunately, C-tethered substrates could not be converted into the desired bicyclo[4.3.1]decane cycloadduct and no reaction took place even after performing this reaction at 100 8 8C( entry 14). The O-tethered substrate 1o was also not suitable for this transformation and the complex mixture was generated when treating 1o under the standard reaction conditions (entry 15).…”
mentioning
confidence: 99%
“…In 2017, a novel Rh(I)-catalyzed intramolecular bridged [5 + 2] cycloaddition of cis-allene-VCPs 223 was developed to synthesize the challenging bicyclo[4.3.1]decane skeletons 225 (Scheme 38g). 100 Preliminary DFT calculations revealed that the inverse allene insertion was favored over the expected normal [5 + 2] cycloaddition in order to reduce the repulsion between the allene and VCP moiety in the transition state 224, Similar to VCPs, allenylcyclopropanes are also active intermediates in Rh(I)-catalyzed cycloadditions. In 2011, the Tang group reported an interesting example that involved the generation of allenylcyclopropanes in situ (Scheme 41).…”
Section: Applicationsmentioning
confidence: 99%
“…Another interesting transformation is the cycloisomerization of allenylcyclopropanes with alkenes from the Mukai group (Scheme 19). 44 The expected [5+2] product is not formed when tethered alkenes are used, and instead the fused 5,6-bicyclic compound 116 is produced which is decorated with two methyl groups and has three contiguous stereocenters that are all cis to each other. An additional unique .…”
Section: Additional Annulations and Cyclizationsmentioning
confidence: 99%